KADAR TANIN BIJI PINANG (ARECA CATECHU L) BERDASARKAN LAMA PEMANASAN DAN UKURAN SERBUK - Karina, .; Indrayani, Yuliati; Dirhamsyah, M. (Universitas Tanjungpura, 2016)
Areca nut plant (Areca catechu L) had been used for adhesive medicine and tanner. Areca nut plant contained many tannins in the seed. Tannin was a component of organic substance which was very complex, consists of fenolic compound which was difficult to be separated and cristalize, precipate the protein from solution and compound with protein. This research purposed to know the influence of the heating lenght and optimum dust size along with the interaction of two factors above toward the level of tannin areca nut seed. This research was experiment used extraction method with the heating length about 2 hours, 3 hours, and 4 hours along with the dust size about 60 mesh, 80 mesh, and 100 mesh. The extract was tested to establish the highest level of active tannin. The result of various analysis investigation showed that the factor of heating length and dust size along with the interaction of two factors above were not influential toward the level of active tannin.Â The level of optimum active tannin attained on the heating length about 3 hours with the dust size 80 mesh in the mount of 11,0022%. Keywords : Areaca nut, tannin, heating length